Disentangling Litter Size and Farrowing Duration Effects on Piglet Stillbirth, Acid–Base Blood Parameters and Pre-Weaning Mortality - van den Bosch, Moniek; van de Linde, Irene B.; Kemp, Bas; van den Brand, Henry (Frontiers in Veterinary Science, 2022)
The current study evaluated interactions between farrowing duration and litter size on the level of asphyxia, vitality, percentage of stillbirth and pre-weaning mortality of piglets. Farrowing duration was measured in 159 crossbred gilts and sows (Yorkshire x Dutch Landrace). Litter size ranged between 12 and 21 piglets. Blood acid-base parameters in umbilical cord blood and vitality scores of piglets were determined immediately after birth. Number of piglets born alive and stillborn as well as individual piglet weights at birth were recorded. Pre-weaning mortality (excl. stillbirth) was determined throughout lactation. Litter size as well as farrowing duration were categorized to evaluate the interaction between the two. There tended to be an interaction between litter size and farrowing duration for pre-weaning mortality (P = 0.10). In small litters (12-15 piglets), a prolonged farrowing duration (> 250 min) tended to increase pre-weaning mortality compared to a short (< 150 min) and medium farrowing duration (150-250 min), while for large litters (19-21 piglets) a medium to long farrowing duration tended to decrease pre-weaning mortality. No other interactions between litter size and farrowing duration were found. Piglets within large litters showed a higher umbilical cord lactate level (P < 0.01), lower average vitality score (P = 0.01) and a higher stillborn percentage (P < 0.01) compared to piglets within medium size (16-18 piglets) and small litters. Each additional piglet born to a litter linearly decreased average piglet birth weight (17.6 g, P < 0.01), increased farrowing duration (11 min, P < 0.01) and increased stillbirth (0.5%, P = 0.04). A medium farrowing duration resulted in a lower stillborn percentage compared to a short or prolonged farrowing duration, suggesting that farrowing duration might have an optimum. When analyzed linearly, stillborn percentage increased with 1.85% per every 100 min (P < 0.01) of farrowing duration. It can be concluded that both litter size and farrowing duration affect stillborn percentage, but independent from each other. However, these two factors tended to interact regarding pre-weaning mortality, suggesting that setting a certain threshold for maximal farrowing duration should be taken with care, because this appears to depend on litter size.